Keefektifan Metode Field Trip Dalam Keterampilan Berbicara Bahasa Jerman - Anisa Putri; Syukur Saud; Muh. Anwar (Universitas Negeri Makassar, 2021)
Abstract. The purpose of this study was to obtain data and information about students' speaking skills using the Field Trip method. The purpose of this study was to obtain data and information about students' speaking skills using the Field Trip method. This study uses a true experimental design. Data were analyzed by inferential statistical analysis with t-test. The population of this study were students of class XI MAN 1 Makassar which consisted of six classes of 150 students. The Samples was 40 students, namely 20 students of class XI MIA 1 as the experimental class and 20 students of class XI MIA 3 as the control class. The sample used is a random sampling. The results of data analysis showed t count 3.8 > t table 2.03 at a significance level of 0.05. The results showed that the use of the Field Trip method was effective in speaking skills of class XI students of MAN 1 Makassar.